Hopewell junction : a railroader's town : a history of short-line railroads in Dutchess County, New York - Rudberg, Bernard L.; Desmond, John Michael (State University of New York Press, 2022)
Hopewell Junction: A Railroader's Town tells the remarkable history of the east-west, short-line railroads that ran throughout Dutchess County, New York from 1869 to 1984, centering on the hamlet of Hopewell Junction. It explains how these lines transformed the rural countryside and supercharged the growth of the agricultural and small-mill communities of Dutchess County during the last half of the nineteenth century and throughout most of the twentieth century. The story includes a group of hardscrabble pioneers who struggled to establish their own rail networks. It relates the innovations in design and construction that made these lines possible and the challenges posed to their success by accidents, bad weather, and bad luck. After World War II, new modes of transportation and the growth of suburbia lead to the decline and eventual abandonment of many of these rail lines. However, a group of dedicated local historians and citizens banded together to make sure that this history was preserved, including the restoration of the historic depot at Hopewell Junction, listed as a historic and architectural resource on the New York State Register of Historical Places in 2020 and on the National Register of Historic Places in 2021.
Keywords: Railroads -- New York (State) -- Dutchess County -- History.; Railroad law -- New York (State) -- Dutchess County.; Dutchess County (N.Y.) -- History.; Chemins de fer -- New York (État) -- Dutchess -- Histoire.; Railroad law; Railroads; New York (State) -- Dutchess County; history (discipline); e-books.; History